An Evaluation of Italian Midwives' Knowledge of Stillbirth Clinical Management, Bereavement Care and Prevention of Recurrences: A Post-Hoc Analysis of the BLOSSoM Study - Claudia Ravaldi; Laura Mosconi; Elisa Carelli; Aurora Frontini; Sara Tagliavini; Eleonora Cossu; Francesca Monari; Fabio Facchinetti; Alfredo Vannacci (Clinical and Experimental Obstetrics & Gynecology)
Background: In several countries a gap is still present between evidenced-based stillbirth care guidelines and the actual care that parents receive. Knowledge of international guidelines is the first step to give respectful care when a perinatal death occurs. Parents’ trauma could in fact be worsened by inadequate support from health care professionals (HCPs) during and after hospitalisation. Aim of this study is to analyse the knowledge of Italian midwives about the main aspects of clinical management included in international stillbirth guidelines. Methods: The subject of this paper is a post-hoc analysis of the BLOSSoM study. In particular, descriptive statistics was used to analyse the items of Lucina questionnaire (a section of the BLOSSoM study) linked to clinical management of perinatal loss. Results: Four areas of clinical management included in international guidelines were investigated: (1) bereavement care, (2) pharmacological management and aftercare, (3) post-mortem procedures and rituals, and (4) pattern of fetal movements. In the first area, most midwives showed a lack of knowledge particularly regarding natural inhibition of lactation (22.5%) and milk donation (18%). Pharmacological management was characterised by a relevant use of sedatives and analgesia during both labour (38.4% and 89.3%) and childbirth (26.3% and 65.6%). Regarding post-mortem procedures, more than half midwives were not fully aware of Italian law on funerals and related matters, and 37.1% thought that the baby was disfigured during post-mortem examination. Only 30% of the sample answered correctly to the items about the characteristics of healthy fetal movements pattern. Finally, a multivariate analysis was performed to identify independent factors predictive of high knowledge of international guidelines. The variables taken into account were: age, years of work, number of stillbirths assisted, presence in the hospital of a specific protocol and personal training on stillbirth management. Only the last one was significantly associated with a high knowledge of guidelines. Conclusions: Italian midwives are still not fully aware of international guidelines on stillbirth management. The definition of national guidelines endorsed by scientific societies, as well as specific training courses for midwives in Italian hospitals, could be the first steps to improve clinical and psychological management of perinatal loss.